AN APPLICATION OF UTAUT2 MODEL IN EXPLORING THE IMPACT OF QUALITY OF TECHNOLOGY ON MOBILE INTERNET - Amra Kraljić; Almir Peštek (Economic Review)
The purpose of this paper is to explore the adoption of mobile Internet in a developing country. This paper presents an application of the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) model. The model was adapted with a construct Quality of Technology (QT) represented by four variables. The aim of this study was to find out what impact QT has on the use of mobile Internet moderated by Gender, Age and Experience. The research was conducted in two phases: a pilot study and a quantitative survey. The pilot study aimed to test the validity and reliability of the questionnaire. The sample for the pilot study consisted of 80 respondents. The sample of 562 respondents was used for the quantitative survey. The Structural Equation Model (SEM) that includes confirmatory factor analysis, path analysis, partial least squares analysis and modelling latent variables was used for the analysis. The results confirmed that QT has a significant impact on the use of mobile Internet. The analysis showed that older users are more sensitive to the use of mobile Internet. Furthermore, the research confirmed that gender does not have a significant impact on the relation between QT and the use of mobile Internet. The impact of QT on the use of mobile Internet is higher for more experienced users. This paper confirmed that the adapted UTAUT2 model extended with QT can be used for exploring the adoption of mobile Internet in a country in transition. It recommends the application of this extended model in other developing countries with the purpose of testing its relevance. The research will fill a gap in the theory of user acceptance of technology due to the fact that UTAUT2 has not been applied in Bosnia and Herzegovina and that the models of user acceptance of technology have not so far treated QT.